Effectiveness of Health Education Using Booklet & Video on Knowledge of Pregnancy Danger Signs Among Primigravida Mothers - Khairah, Rahayu; Dewi, Linda; Aliyah, Nur; Nurfikah, Nunung (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims : The aims of this study was to see the effectiveness of providing pregnancy danger sign videos and education through KIA books on the knowledge of pregnant women about pregnancy danger signs. Methods : The study conducted in May-June 2023, involved 180 pregnant women, 90 receiving video intervention on pregnancy danger signs and 90 receiving MCH book education, and used a questionnaire for bivariate analysis. Results : Mann-Whitney test in the video group are Sig.2-tailed of 0.000 <0.05, then the provision of educational videos is effective in increasing the knowledge of pregnant women about the danger signs of pregnancy and statistically significant. Conclusions : The Mann-Whitney test showed that educational videos effectively increase pregnant women's knowledge about danger signs of pregnancy, while MCH book education was found to be insignificant. The results suggest that educational videos are effective in raising awareness.